2010
DOI: 10.1090/s0025-5718-09-02231-5
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of nonlinear wave equations with nonstandard anisotropic growth conditions

Abstract: Abstract. Weak solutions for nonlinear wave equations involving the p(x)-Laplacian, for p : Ω → (1, ∞) are constructed as appropriate limits of solutions of an implicit finite element discretization of the problem. A simple fixed-point scheme with appropriate stopping criteria is proposed to conclude convergence for all discretization, regularization, perturbation, and stopping parameters tending to zero. Computational experiments are included to motivate interesting dynamics, such as blowup, and asymptotic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The proof of this theorem goes exactly like that of Theorem . More on the local and global existence can be found in Antontsev and Haehnle and Prohl…”
Section: Preliminariesmentioning
confidence: 62%
“…The proof of this theorem goes exactly like that of Theorem . More on the local and global existence can be found in Antontsev and Haehnle and Prohl…”
Section: Preliminariesmentioning
confidence: 62%
“…Indeed, it is necessary, for such a numerical study, to approach p(x) by some piecewise constant or piecewise polynomial functions p h (x), h being the discretization parameter (see e.g. Haehnle and Prohl [37] and the forthcoming paper [7] for numerical approximation of problems involving p(x)-laplacian).…”
Section: P(•)mentioning
confidence: 99%
“…In what concerns the passage-to-the-limit techniques, Zhikov's methods include semicontinuity arguments and an ingenious adaptation of the classical Minty-Browder monotonicity argument; see in particular [68,Lemmas 8,9]. Similar approaches were used by Haehnle and Prohl [37] and by Wróblewska (see [62] and references therein). Our argument is longer but more straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…[11,13,27,28], and the literature cited therein. Evolutionary equations with nonstandard anisotropic growth conditions have been investigated both, analytically and numerically in [1,2], and [26,17]. In this work, we present an implicit finite element discretization of (1.8)-(1.11), which is referred to as Scheme A, for variable p ∈ C Ω, (1, ∞) .…”
Section: Introductionmentioning
confidence: 99%
“…(1.1)-(1.4)). The numerical analysis combines tools which have been developed in [7] for constant p's, and in [26,17] for the numerical study of related evolutionary problems with nonstandard anisotropic growth conditions. Computational studies, both academic and with applications in computational fluid dynamics, are reported in Section 5.…”
Section: Introductionmentioning
confidence: 99%